Selective response to iron and epo signals of iron cycle proteins in a mouse model - Fernandez Delias, María Florencia (2020)
The Erythropoietin (EPO) is associated with iron mobilization.The aim was to analyze the regulatory relationship between iron and EPO studying iron key proteins in several tissues in an animal model of iron overload and EPO. CF1 mice divided into groups (n= 4/group): 1) Iron-adequate (IA); 2) Iron-overload (IO) (iron saccharate; days 0, 4, 8, and 12 i.p. ; 1,800 mg/kg) ; 3) EPO (days 17, 18, and 19) i.p. ; 20,000 UI/kg); 4) Iron overload+EPO (IO+EPO). Immunohistochemistry: anti-DMT1 (divalent metal transporter1) and ZIP14 (Zrt-Irt-like Protein14). Perl´s staining. Iron levels: Wiener kit. The Protocol was approved by CICUAE-UNS. Our data demostrated that the protective action of EPO against IO was selective in several tissues responding to different signals as follows. In lung: both DMT1 and ZIP 14 response to “EPO signal”. Interestingly was observed that DMT1 localization in bronchial cells was changed being cytoplasmic in IA/IO+EPO/EPO, while it was localized in membrane cell and apical zone in IO condition. ZIP14 expression was dowregulated by “EPO signal” in bronchial cells. In spleen: both importers were downregulated by “EPO signal”. Conversely, hepatic tissue responds to iron signal. Hepatic DMT1 and ZIP14 were dowregulated and upregulated, respectively. On contrary,in pancreas a selective importers response to “iron/EPO signal” was observed. In fact, DMT1 expression in Langerhans islets was downregulated by iron signal, however in acini ZIP14 was downregulated by “EPO signal”. In all tissues Iron level was significant higher in the IO respect to IA and a significant decrease in IO+EPO respect to IO. The protective action of “EPO signal” against IO in all studied tissues could be explain by the reduced iron uptake in spleen, lung and pancreas. Nevertheless, the prevalence of the “iron signal” in liver may be explained by the increased hepatic iron uptake through ZIP14, thus reducing iron systemic level. Understanding the relations between these proteins will contribute to extend our knowledge in the field of iron and erythropoiesis.